Math, asked by zakirkhanbld, 8 months ago

Subtract (4y - 9) from (3y
Try it!
EXER
1. Simplify the following expressions.
(a) -(-2a + 7) (b) -(46-c-5d)
(c) -5 + (7k + 3) (d) m - (8m - 9)​

Answers

Answered by Anonymous
1

Step-by-step explanation:

Subtraction

3y - ( -4y + 9 )

3y + 4y - 9

7y - 9

Simplify

  • minus*minus=plus
  • plus*plus=plus
  • minus*plus=minus
  • plus*minus=minus

a) 2a -7

b) -46 + c + 5d

c) -5 + (7k + 3)

-5 + 7k + 3

-2 + 7k

d) m - 8m + 9

-7m + 9

Hope it helps

Similar questions